2016
DOI: 10.4236/ijg.2016.74038
|View full text |Cite
|
Sign up to set email alerts
|

Petrochemistry of Two Magnetite Bearing Systems in the Precambrian Belt of Southern Cameroon

Abstract: In the past decades, several iron ore occurrences have been discovered in the Precambrian Belt of southern Cameroon, with focus on their economic potential, and little attention on the deposit type. However, few studies have been geared towards understanding the different deposit types within this region. This paper seeks to provide new insight on the different styles of iron ore mineralisation of two potential, yet least studied iron ore deposits in this region in addition to enhancing exploration efforts wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…The magnetite gneisses have total Fe 2 O 3 values between 40.8 and 48.0 wt-% and SiO 2 values between 34.7 and 53.4 wt-% which are comparable to the total Fe 2 O 3 and SiO 2 values obtained for similar iron formations in the Nyong area (Ndong et al 2016; Ngoran et al 2016; Ganno et al 2017). The values are also comparable to that of fresh quartz BIFs from other deposits around the world (Spier et al 2003; Klein and Ladeira 2004; Suh et al 2008; Suh et al 2009; Nforba et al 2010).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The magnetite gneisses have total Fe 2 O 3 values between 40.8 and 48.0 wt-% and SiO 2 values between 34.7 and 53.4 wt-% which are comparable to the total Fe 2 O 3 and SiO 2 values obtained for similar iron formations in the Nyong area (Ndong et al 2016; Ngoran et al 2016; Ganno et al 2017). The values are also comparable to that of fresh quartz BIFs from other deposits around the world (Spier et al 2003; Klein and Ladeira 2004; Suh et al 2008; Suh et al 2009; Nforba et al 2010).…”
Section: Discussionsupporting
confidence: 71%
“…This study provides preliminary chemical data directly targeting the magnetite minerals compared to previous dominantly whole-rock geochemical studies on iron formations in the Nyong Unit (Ndong et al 2016; Ngoran et al 2016; Ganno et al 2017). The studies elucidate the significant hydrothermal source of magnetite mineralisation in the Nyong Unit and therefore suggest a succinct interpretation of the structural data in combination with geophysical and geological data to guide drill hole locations, as these features provide the necessary conduits for hydrothermal fluid circulations and eventual enrichment.…”
Section: Discussionmentioning
confidence: 89%
“…Hydrothermal alteration in the Ntem complex has been recognised by recent works at the vicinities of the study area (in areas subject to advanced mineral exploration works) which also showed that hydrothermalism occurred in the Ntem Complex in a shallow seawater, probably in a subduction context [106] [107] [108] [109]. Porphyry as a subclass of hydrothermal deposits, is associated with one or various intrusions of felsic to intermediate rocks [4] [110] [111] as it is the case in this portion of the Ntem Complex made up of TTG granites, granodiorites [41] [47].…”
Section: Hydrothermal Alteration Mapping and Mining Implicationsmentioning
confidence: 82%
“…lithological and structural context pertaining to this study area, hydrothermalism and absence of Cu would infer a Kiruma-type deposits [113]. However, [106] evidence of a Ba, Cu, Zn and V enriched iron oxide deposit suggests the existence of skarn or porphyry deposit nearly 45 km west of the study area (Binga project). Our results match with the existence of IOCG and porphyry/skarn ore deposits east and northeast Brazil [3] [4] [114].…”
Section: Hydrothermal Alteration Mapping and Mining Implicationsmentioning
confidence: 85%
“…Very little progress has been achieved in Cameroon's iron mineralization research, despite several studies and discoveries by academics and mining companies. This is occurring in southern Cameroon, especially in the areas of Mbalam, Mamelles, Nkout, Ngovayang, Meyongo, and Mayo-Binka in the Ntem Complex, on the northern edge of the Congo Craton [13][14][15][16][17][18][19][20][21][22]. But because the origin of iron mineralization still has to be determined, there are still some places where the search for iron mineralization has not yet advanced.…”
Section: Introductionmentioning
confidence: 99%